Decreased expression of TCF12 contributes to progression and predicts biochemical recurrence in patients with prostate cancer - Qing-biao Chen; Ying-ke Liang; Yan-qiong Zhang; Min-yao Jiang; Zhao-dong Han; Yu-xiang Liang; Yue-ping Wan; Jie Yin; Hui-Chan He; Wei-de Zhong (Tumor Biology)
As a member of helix–loop–helix protein family, transcription factor 12 functions as either an oncogene or a tumor suppressor in various human cancers. However, there are no reports on its involvement in prostate cancer. To investigate clinical relevance of transcription factor 12 in prostate cancer and to evaluate its roles in malignant phenotypes of this cancer in vitro and in vivo, we here examined expression patterns of transcription factor 12 protein in 50 prostate cancer tissue specimens by immunohistochemistry. Then, associations of transcription factor 12 expression with various clinicopathological characteristics and patients’ prognosis of prostate cancer were evaluated. Its involvements in cancer cell proliferation, migration, invasion, and tumor growth were determined by in vitro and in vivo experiments. As a result, the positive immunostaining of transcription factor 12 protein was localized in cytoplasm and/or nucleus of prostate cancer cells. Its expression levels were decreased with prostate cancer Gleason score increased. Statistically, the decreased expression of transcription factor 12 protein more frequently occurred in prostate cancer patients with high Gleason score, positive metastasis, prostate-specific antigen failure, and short biochemical recurrence–free survival (all p < 0.05). Importantly, multivariate analysis showed that the status of transcription factor 12 expression was an independent predictor of biochemical recurrence–free survival in prostate cancer. Functionally, enforced expression of transcription factor 12 suppressed cell proliferation, migration, and invasion in vitro and inhibited tumor growth in vivo. In conclusion, transcription factor 12 protein may be a novel molecule which plays a critical role in prostate cancer progression and patients’ prognosis, suggesting it might be a promising therapeutic target for prostate cancer therapy.